The Causes of Perestroika in the USSR (Dedicated to the 30th Anniversary of the Term “Perestroika”) - Svetlana A. Velichko (Сибирское юридическое обозрение)
The article discusses the main causes of perestroika from the point of view of the theory of democratic transit. It is proved that the USSR by the mid 80-s had reached a level of income per capita at which democratic transition is possible. The author substantiates economic, social and cultural preconditions of perestroika.